International Cooperation in EU Pre-Trial Investigations and Its Future Role in Ukraine’s Legal Reform - Kozachenko, Oleksandr I.; Zarosylo, Volodymyr; Gelemei, Mykola O.; Stankovych, Mykhailo I.; Yatsun, Mykola M. (Journal of Law and Legal Reform, 2024)
This article examines international cooperation between law enforcement agencies within the European Union (EU) during pre-trial investigations, guided by the Association Agreement between Ukraine and the EU. Special focus is placed on the European Arrest Warrant (EAW), analyzing its application, efficiency, and implications for Ukraine’s prospective EU membership. The study emphasizes the need for Ukraine to align its legal framework with EU standards, considering the issuance and execution of EAWs. As Ukraine aims to become an EU member state, it must understand and comply with the procedures and best practices associated with these warrants. Despite the existing legal frameworks, challenges remain due to the lack of consistent practice across EU countries in issuing and executing the EAW. This research identifies key areas where Ukraine can improve its legal reforms to align with EU practices, particularly concerning EAW implementation. Recommendations include a detailed analysis of the EAW application process that accounts for the nuances of national legislation while adhering to EU regulations. By understanding these complexities and bridging legal gaps, Ukraine can effectively navigate the challenges and enhance international cooperation in criminal investigations. Ultimately, this article provides practical insights and policy recommendations to ensure Ukraine’s successful integration into the EU’s legal framework for pre-trial investigations. It highlights the importance of adopting best practices in the issuance and execution of the EAW, emphasizing the need for legal reforms that respect national peculiarities without contravening EU law.